Direct tuning of soliton detuning in an ultrahigh-Q MgF2 crystalline resonator - Wang Heng; Duan Bing; Wang Kai; Wu Xing-Yu; Gao Yong-Pan; Lu Bo; Yang Daquan; Wang Chuan (Nanophotonics, 2023)
The dissipative Kerr soliton combs based on microresonators have attracted wide attention due to their high coherence and on-chip integration. Meanwhile, the soliton microcombs have shown broad applications in coherent communication, on-chip low-noise microwave synthesizer, optical clock, etc. However, the performance of these applications is typically limited by their bandwidth as the precise tuning of the soliton microcombs usually relies on the thermoelectric cooler, which is slow and may increase the system’s complexity. Here, we demonstrate the observation of dissipative solitons based on the magnesium fluoride resonator with an ultrahigh-quality (Q) factor of about 927 million. The ‘power-kicking’ scheme is employed to lock and stabilize the solitons actively. Also, tuning the acousto-optical modulator allows changing the bandwidth and recoil of the solitons. This approach enables more direct and concise feedback and reduces the system’s complexity.